Microscopia eletrônica de varredura de fungos nematófagos associados a tylenchulus semipenetrans e pratylenchus jaehni - Martinelli, Paulo Roberto Pala [UNESP]; dos Santos, Jaime Maia [UNESP] (My University, 2010)
Nematophagous fungi have been studied as a promising alternative for the management of nematodes of citrus. This study had the objective of documenting by scanning electron microscopy the outslading morphological structures for the identification of the main species of nematophagous fungi involved in the study and proving the pathogenicity of the isolated ones associated with T. semipenetrans and P. jaehni, Isolated came from in citrus orchards, mainly in São Paulo State, were studied in the Laboratory of Scanning Electron Microscopy of FCAV/UNESP - Campus de Jaboticabal-SP. The data obtained in this study have confirmed that the scanning electron microscopy is an effective tool to assist in the understanding of way of action of the nematophagous fungi: Arthrobotrys oligospora, A. conoides, A. robusta, A. musiformis, Dactylella leptospora, Monacrosporium eudermatum and M. elegans and to revealdetails of their reproductive structures and the capture, to confirm the pathogenicity of the isolated to T. semipenetrans and P. jaehni, as well as to confirm the identification of some isolated.
Scanning electron microscopy of nematophagous fungi associated tylenchulus semipenetrans and pratylenchus jaehni
Keywords: Arthrobotrys spp. monacrosporium spp; Pratylenchus jaehni; Predator fungi; Scaning electron microscopy; Tylenchulus semipenetrans